The Developmental Processes of Forgiveness in Adults Learners - Perdeta Bush (Adult Education Research Conference, 2014)
Models of forgiveness give insight into the development of the adult learner as they make meaning of an offense as well as the value they place on the forgiving process. Two models that explore the processes and establish the conditions in which adults learn to forgive are discussed. Both models allow for the learner to navigate their experience according to their own personal development and the context of the offense.